Shotgun proteomics profiling of chia seeds (Salvia hispanica L.) reveals genotypic differential responses to viability loss - Rodríguez, María Emilia; Poza-Viejo, Laura; Maestro-Gaitán, Isaac; Schneider-Teixeira, Aline; Deladino, Lorena; Ixtaina, Vanesa; Reguera, Maria (Frontiers in Plant Science, 2024)
Exposure to elevated temperatures and relative humidity expedites the seed aging process, finally leading to seed viability loss. In this context, certain proteins play a pivotal role in safeguarding the longevity of seeds. However, the seed proteomic response to loss viability in Salvia hispanica L., commonly known as chia, remains incompletely understood. This work explores the application of proteomics as a potent tool for uncovering molecular responses to viability loss caused by artificial aging in two chia genotypes, WN and MN. By using a quantitative label-free proteomics analysis (LC-MS/MS), 1787 proteins were identified in chia seeds at a 95% confidence level, including storage proteins, heat shock proteins (HSPs), late embryogenesis abundant proteins (LEA), oleosins, reactive oxygen species (ROS)-related enzymes, and ribosomal proteins. A relatively low percentage of exclusive proteins were identified in viable and non-viable seeds. However, proteins exhibiting differential abundance between samples indicated variations in the genotype and physiological status. Specifically, the WN genotype showed 130 proteins with differential abundance comparing viable and non-viable seeds, while MN displayed changes in the abundance of 174 proteins. While both showed a significant decrease in key proteins responsible for maintaining seed functionality, longevity, and vigor with high-temperature and humidity conditions, such as LEA proteins or HSPs, ROS, and oleosins, distinct responses between genotypes were noted, particularly in ribosomal proteins that were accumulated in MN and diminished in WN seeds. Overall, the results emphasize the importance of evaluating changes in proteins of viable and non-viable seeds as they offer valuable insights into the underlying biological mechanisms responsible for the maintenance of chia seed integrity throughout high-temperature and humidity exposure.